KINETICS OF PERCOLATION OF DISPERSE MEDIA - Nesterov I.I.; Shantarin V.D.; Arinshteyn E.A.; Voytenko V.S. (My University, 1988)
Analysis of kinetics of filtration of dispersions through rock walls in oil-well drilling is becoming important for evaluating and developing methods of control of properties of such systems in order to assume stability of wells, effective penetration of productive strata, and increased yields of oil which depend on the thickness h the strength and the rate of formation h(t) of a deposited mud (filter) cake, all of these being experimentally-determined quantities. The absence of an analytical equation for h(t) hinders the a priori determination of these quantities from the engineering properties of dispersed systems and their behavior during the drilling process. This paper attempts to define the function h(t) on the basis of a model of a moving solid-phase boundary in the course of filtration of a disperse system.